Cultivation of deep-sea bacteria from the Northwest Pacific Ocean and characterization of Limnobacter profundi sp. nov., a phenol-degrading bacterium - Kim, Mirae; Song, Jaeho; Shin, Seung Yeol; Kogure, Kazuhiro; Kang, Ilnam; Cho, Jang-Cheon (Frontiers in Marine Science, 2024)
Despite previous culture-independent studies highlighting the prevalence of the order Burkholderiales in deep-sea environments, the cultivation and characterization of deep-sea Burkholderiales have been infrequent. A total of 243 deep-sea bacterial strains were isolated from various depths in the Northwest Pacific Ocean, with 33 isolates (13.6%) from a depth of 4000 m classified into Burkholderiales. Herein, we report the isolation and genome characteristics of strain SAORIC-580 T , from a depth of 4000 m in the Northwest Pacific Ocean. The strain showed a close phylogenetic relationship with Limnobacter thiooxidans CS-K2 T , sharing 99.9% 16S rRNA gene sequence identity. The complete whole-genome sequence of strain SAORIC-580 T comprised 3.3 Mbp with a DNA G+C content of 52.5%. Comparative genomic analysis revealed average nucleotide identities between 79.4-85.7% and digital DNA-DNA hybridization values of 19.9-29.5% when compared to other Limnobacter genomes, indicating that the strain represents a novel species within the genus. Genomic analysis revealed unique adaptations to deep-sea conditions, including genes associated with phenol degradation, stress responses, cold adaptation, heavy metal resistance, signal transduction, and carbohydrate metabolism. The SAORIC-580 T genome was found to be more abundant in the deep sea than at the surface in the trenches of the Northwest Pacific Ocean, suggesting adaptations to the deep-sea environment. Phenotypic characterization highlighted distinct differences from other Limnobacter species, including variations in growth conditions, enzyme activities, and phenol degradation capabilities. Chemotaxonomic markers of the strain included ubiquinone-10, major fatty acids such as C16:0, C16:1, and C18:1, and major polar lipids including phosphatidylethanolamine, phosphatidylglycerol, and diphosphatidylglycerol. Based on the polyphasic taxonomic data, it is concluded that strain SAORIC-580 T (= KACC 21440 T = NBRC 114111 T ) represents a novel species, for which the name Limnobacter profundi sp. nov. is proposed.